Determinan Kejadian Diare pada Bayi di RSIA Az Zahra Kota Palembang - Yemmy Putri Sari; Hafizotun Hasanah (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Diarrhea is a significant health concern among infants, especially those aged 0–6 months, and can lead to serious consequences if not managed properly. The occurrence of diarrhea is influenced by factors such as maternal characteristics and infant feeding practices. This study aimed to analyze the determinants of diarrhea among infants aged 0–6 months at RSIA Az Zahra Palembang. A descriptive analytic design with a cross-sectional approach was used, involving 254 infants who experienced diarrhea at RSIA Az Zahra Palembang from January–October 2024. A sample of 70 respondents was selected using the Lemeshow formula and random sampling. Data analysis was conducted with univariate and bivariate analyses, including the Chi-square test. The results showed that most mothers were in early adulthood (92.9%), had a senior high school education (60.0%), and were employed (87.1%). Most infants (88.6%) were formula-fed. Bivariate analysis revealed that maternal education, maternal occupation, and formula feeding were significantly associated with diarrhea (p < 0.05), while maternal age was not (p > 0.05). Formula feeding was the most dominant factor associated with diarrhea. In conclusion, maternal education, occupation, and formula feeding influence the occurrence of diarrhea in infants, with formula feeding being the most significant factor. Enhancing health education on exclusive breastfeeding and hygienic formula feeding is crucial in preventing diarrhea.